Peranan Koperasi Simpan Pinjam (KSP) Payana Mandiri Dalam Upaya Meningkatkan Kesejahteraan Anggota Di Desa Samuan Carangsari - Suardika, I Ketut Nik; Putra, I Komang Trisna Eka; R S, Aditya Manggala; Sugiartana, I Wayan (Universitas Tabanan, 2025)
This study aims to determine the role of the Payana Mandiri savings and loan cooperative in improving economic welfare in Samuan Carangsari village. This study uses a qualitative method with a descriptive approach by describing and explaining in detail the problems to be studied based on data obtained previously through research reports in the form of observations, structured interviews and documentation called Triangulation Data collection techniques. Triangulation Data collection techniques in this study are testing the credibility of the data by checking the data with the source using interview techniques to the source and then checking with direct observation of the Payana Mandiri savings and loan cooperative to ensure that the data obtained is correct and valid. Data sources can be taken from the chairman, secretary and members of the Payana Mandiri savings and loan cooperative. From the results of this Triangulation data collection technique study, the researcher was able to find out that the Payana Mandiri savings and loan cooperative plays a very important role in efforts to improve economic welfare in Samuan Carangsari village, as evidenced by the many cooperative members who are assisted in capitalizing small members so that they are able to get out of poverty. With the presence of the Payana Mandiri savings and loan cooperative in the midst of the members of Samuan Carangsari Village, it will provide easier financial solutions, education will be easier to access, and the implementation of religious worship or ceremonies will run well and even be able to meet the needs of its members, both clothing, food and health.